THE EFFECT OF GREEN INVESTMENT, GOVERNMENT POLICY, AND RESOURCE MANAGEMENT ON THE FINANCIAL PERFORMANCE OF START-UPS IN CENTRAL JAWA - Utami, Eva Yuniarti; Ayuni, Risca Fitri; Nuvriasari, Audita; Uli, Nur Zarliani; Pratama, Rohmawan Adi (Jurnal Manajemen Bisnis dan Terapan, 2024)
Indonesia, has become a hub for such start-ups, aiming for both financial success and environmental consciousness. Green investments, which fund projects with environmental benefits, play a crucial role. These investments range from adopting energy-efficient technologies to implementing sustainable supply chains, leading to long-term cost savings and improved corporate reputation.Government policy is also vital, as supportive policies in Central Java include monetary rewards, tax breaks, and assistance programs that encourage start-ups to adopt sustainable practices. Effective resource management, which optimizes the use of human, financial, and material resources, is crucial for start-ups facing limited resources and intense competition. Efficient resource management can significantly impact a start-up’s operational efficiency and financial outcomes.This study examines how green investments, government policy, and resource management collectively influence the financial success of start-ups in Central Java. Data was collected from 40 start-ups across various industries using a quantitative approach, and multiple regression analysis was performed. The results show that higher financial performance is primarily due to green investments, supportive government policies, and efficient resource management, with a positive interaction between these factors leading to significant gains. The study provides factual proof that effective resource management, sustainable practices, and compliance with government regulations are essential for successful start-up operations. It highlights the complementary effects of these elements, suggesting that a comprehensive corporate strategy enhances financial results. This study offers insights for start-ups to enhance sustainability and performance and provides recommendations for policymakers to create a supportive entrepreneurial environment.